PENGARUH LATIHAN PLYOMETRIC FRONT BOX JUMP TERHADAP KEMAMPUAN SMASH PADA PERMAINAN BOLA VOLI SISWA KELAS XI SMAN 1 SAMPARA - Nurkomaria; Asmuddin; La Ode Rusdin (Journal Olympic (Physical Education, Health and Sport), 2021)
The purpose of this study was to determine the effect oftraining front box jump plyometric onability smash in volleyball games for class XI students of SMA Negeri 1 Sampara. The population in this study were all students of class XI SMA Negeri 1 Sampara, totaling 225 people who were then selected by purposive sampling based on gender considerations, students who could do plyometric front box jumps and students who could do smash. Based on the above considerations, the results of the selection were 20 people. The training program was plyometric front box jump carried out for 6 weeks with a frequency of 3 times a week. The test instrument used in this study was a test to do a smash with a ball that was hit and entered into the field will be counted as points and entered as data in this study. Based on the results of data analysis using t-test, the results obtained tcount= 2.371 ≥ ttable= 1.729 at a significant level of 0.05. In this study, it can be concluded that there is an effect oftraining plyometric front box jump onskills smash in volleyball games for class XI students of SMA Negeri 1 Sampara